Personal bankruptcy and credit market competition - Astrid Dick; Andreas Lehnert (Federal Reserve Bank of New York, 2006)
The effect of credit market competition on borrower default is theoretically ambiguous, because the quantity of credit supplied may rise or fall following an increase in competition. We investigate empirically the relationship between credit market competition, lending to households, and personal bankruptcy rates in the United States. We exploit the exogenous variation in market contestability brought on by banking deregulation at the state level: after deregulation, banks faced the threat of entry into their state markets. We find that deregulation increased competition for borrowers, prompting banks to adopt more sophisticated credit rating technology. In turn, these developments led previously excluded households to enter the credit market. We document that, following deregulation, (1) overall lending increased, (2) loss rates on loans decreased, and (3) bankruptcy rates rose. Further, we find that lending and bankruptcy rates increased more in states with greater actual (rather than potential) entry, and that credit card productivity increased after the removal of entry restrictions. These findings suggest that entrants brought with them enhanced underwriting technology that allowed for credit extension to new borrowers.
Keywords: K3; G2; L1; 330; consumer bankruptcy; banks; competition; Private Verschuldung; Insolvenz; Kreditmarkt; Wettbewerb; USA